1987
DOI: 10.1177/088626087002001003
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs About Rape and Women's Social Roles

Abstract: Researchers dealing with feminist issues have proposed that sexual assaults on women are supported by social beliefs that encourage male domination and exploitation of women. One of the most influential sources for this position is Susan Brownmiller's (1975) social-historical analysis of rape, in which she argues that “rape myths” help support men's social and economical control of women. If this is true, beliefs in rape myths should be positively correlated with beliefs that restrict women's social roles and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 9 publications
4
65
0
Order By: Relevance
“…To assess participants' rape-myth acceptance (RMA), a 10-item version of Bohner's (1998) 'Vergewaltigungsmythenakzeptanz-Skala' (VMAS) was used. The VMAS is a German adaptation of Costin's (1985) R-scale. Item examples are: 'Women often provoke rape through their appearance or behaviour' and 'The defence in a rape trial should not be able to submit as evidence the sexual history of the alleged victim, (reverse scored).…”
Section: Assessment Of Rape-myth Acceptancementioning
confidence: 99%
“…To assess participants' rape-myth acceptance (RMA), a 10-item version of Bohner's (1998) 'Vergewaltigungsmythenakzeptanz-Skala' (VMAS) was used. The VMAS is a German adaptation of Costin's (1985) R-scale. Item examples are: 'Women often provoke rape through their appearance or behaviour' and 'The defence in a rape trial should not be able to submit as evidence the sexual history of the alleged victim, (reverse scored).…”
Section: Assessment Of Rape-myth Acceptancementioning
confidence: 99%
“…It seems reasonable to conclude that in most cases where differences occur, females' judgements are more 'pro-victim', being less likely to blame her, and more likely to convict and more severely punish the rapist. A related finding is that females are less accepting of rape myths (Burt, 1980) than males (Check & Malamuth, 1983;Costin, 1985;Feild, 19786;Giacopassi & Dull, 1986;Muehlenhard & Linton, 1987;Ward, 1988).…”
Section: Subject Differences In Attributionsmentioning
confidence: 99%
“…Also, traditional sex-role attitudes have been found to be related to victim blame for spouse abuse (Kristiansen C(r Giulietti, 1990) and sexual harassment (Malovich & Stake, 1990;Valentine-French & Radtke, 1989), and to attitudes condoning marital rape Ueffords, 1984) and physical abuse (Finn, 1986;Gentemann, 1984;Saunders, Lynch, Grayson & Linz, 1987;Saunders & Size, 1986). Again, a related finding is that traditional sex-role attitudes and rape myth acceptance are related (Check & Malamuth 1983Costin, 1985;Costin & Schwarz, 1987;Feild,.l9786;Hall, Howard & Boetio, 1986;Mayerson & Taylor, 1987;Schwartz & Brand, 1983). Finally, attribution of responsibility has been directly related to rape myth acceptance (Check & Malamuth, 1985;Jenkins & Dambrot, 1987;Krahe, 1788).…”
Section: Subject Differences In Attributionsmentioning
confidence: 99%
“…A number of studies have found that male college students endorse rape myths-beliefs that deny the reality of rape as injurious violence and place the responsibility for heterosexual rape on the woman's behavior-more than female college students (cf. Burt & Albin, 1981;Costin & Schwarz, 1987;Muehlenhard & Linton, 1987). Feild (1978) found the same sex difference in a noncollege sample and Luginbill and Mullin (1981) and Kleinke and Meyer (1990) found that men blamed victims more than women.…”
mentioning
confidence: 81%